2017
DOI: 10.1113/jp273879
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory and decompensatory alterations in cardiomyocyte Ca2+ dynamics in hearts with diastolic dysfunction following aortic banding

Abstract: Key pointsr At the cellular level cardiac hypertrophy causes remodelling, leading to changes in ionic channel, pump and exchanger densities and kinetics.r Previous studies have focused on quantifying changes in channels, pumps and exchangers without quantitatively linking these changes with emergent cellular scale functionality.r Two biophysical cardiac cell models were created, parameterized and validated and are able to simulate electrophysiology and calcium dynamics in myocytes from control sham operated ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…The three models we used are; the Gattoni et al, 2016 (rat) and Luo and Rudy, 1994 (guinea-pig) and O’Hara et al, 2011 human models were selected as being species appropriate, convenient, and fit for purpose. They, and their modifications, have been widely used so there is an extensive literature for comparison ( Viswanatahan and Rudy, 1999 ; Heijman at al., 2011 ; Cardona et al, 2016 ; Gattoni at al., 2017 ; Lee at al., 2017 ; Whittaker at al., 2017 ). Here we use the ORd (2011) model to predict pro- or anti-arrhythmogenic effects in adult human tissue, as CO poses issues in public health and clinical medicine and human in vitro and in vivo electrophysiological data is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The three models we used are; the Gattoni et al, 2016 (rat) and Luo and Rudy, 1994 (guinea-pig) and O’Hara et al, 2011 human models were selected as being species appropriate, convenient, and fit for purpose. They, and their modifications, have been widely used so there is an extensive literature for comparison ( Viswanatahan and Rudy, 1999 ; Heijman at al., 2011 ; Cardona et al, 2016 ; Gattoni at al., 2017 ; Lee at al., 2017 ; Whittaker at al., 2017 ). Here we use the ORd (2011) model to predict pro- or anti-arrhythmogenic effects in adult human tissue, as CO poses issues in public health and clinical medicine and human in vitro and in vivo electrophysiological data is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This rat model will be referred to as “SHAM” throughout the entire work. At the cellular level, ion fluxes and calcium dynamics were simulated using the Gattoni et al [ 5 ] model of rat left ventricular myocyte electrophysiology at 37° and 6 HZ pacing frequency. Active tension generation was described using the Land et al [ 6 ] model of sarcomere contraction, comprising thin and thick filament dynamics, and accounting for sarcomere-length and -velocity dependencies.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, we selected 8 compounds, which were well characterised for multiple ion channels and for which we could find whole organ measurements from literature, from the comprehensive in vitro proarrhythmia assay (CiPA) [ 19 ] official list, namely bepridil, chlorpromazine, diltiazem, mexiletine, nifedipine, ranolazine, sotalol and verapamil, and we described their action at the cell level using a 4-channel description, namely I Na , I to , I K1 and I CaL . I Kr channel was not included as it has a small amplitude in rats myocytes [ 20 ] and so was not included in the employed rat cell model [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous heart models have shown that heterogeneous activation patterns have negligible impact in the small rat heart [11]. Rat ventricular myocytes' Ca 2+ transient was described using the Gattoni et al models [14] for SHAM and AB rats hearts at 37 • C and 6 Hz pacing frequency. Rat cellular contraction was modelled using the Land et al [11] model to simulate tension generation arising from the thin and thick filaments.…”
Section: (B) Rat Heart Modelmentioning
confidence: 99%